Bibliometric Analysis of Birt-Hogg-Dubé Syndrome From 2001 to 2021 - Liu, Shixu; Xia, Kun; Liu, Xiaohong; Duan, Yuanyuan; Hu, Mu; Xia, Hongsheng; Lv, Jiayu; Zhang, Lili; Liu, Yanyi; Xia, Xiao; Li, Guangxi; Cui, Xiangning (Frontiers in Medicine, 2022)
Background: Birt-Hogg-Dubé syndrome (BHD) is a rare autosomal dominant inherited disorder caused by germline mutations in folliculin (FLCN). Despite our significantly evolved understanding of BHD over the past decades, no bibliometric analyses have been conducted in this field. This study aimed to analyze and visualize the characteristics of publication outputs, the research hotspots, and scientific frontiers about BHD using bibliometric analysis. Methods: All relevant literature on BHD was culled from the Web of Science Core Collection (WoSCC) database. Valid data were extracted from the articles and visually analyzed using CiteSpace and VOSviewer. Results: A total of 979 qualifying papers were included. Publication outputs concerning BHD increased over time. The dominant position of the United States and Japan in BHD research was evident. National Cancer Institute (the USA) and Yokohama City University (Japan) were the two most productive organizations. W. Marston Linehan exerted a considerable publication impact and had made the most remarkable contributions in the field of BHD. American Journal of Respiratory and Critical Care Medicine was the journal with the highest publication outputs and impact factor, and nearly all the top 5 journals and co-cited journals belonged to Q1. Keyword citation bursts revealed that management, tumor suppressor, flcn gene, spectrum, diagnosis were the emerging research hotspots. Conclusion: Research on BHD is prosperous. International cooperation between countries and organizations is also expected to deepen and strengthen in the future. Our results indicated that FLCN-associated pathways involved in the pathogenesis of BHD, specific options for early diagnosis, and molecular-targeting therapies will remain research hotspots in the future.